Back Cover: Total Synthesis of Astellatol (Angew. Chem. Int. Ed. 13/2018). Issue 13 (19th February 2018) - Zhao, Nan; Yin, Shuqiang; Xie, Shengling; Yan, Hao; Ren, Pan; Chen, Gui; Chen, Fang; Xu, Jing
Abstract : Chinese paper cutting is a long‐standing tradition, and is often used to decorate doors and windows during the Spring Festival. The Chinese character 福 means blessing and happiness, and the character 春 means spring. With this backdrop, J. Xu et al. present in their Communication onpage 3386 ff., the first enantiospecific synthesis for a three‐decade‐old synthetic challenge, astellatol.